Holocaust and genocide literacy in curricula, textbooks and pupils essays - Carrier, Peter (Policy Briefs, 2022)
Curricula and textbooks play a special role in guiding young people’s understandings of the past, especially when it comes to events that defy explanation, such as those involving extreme violence and mass atrocities. However, informal media provide an ever-growing source of historical knowledge and understanding, which partly supplant formal educational materials and thereby raise two questions: What explanations of the Holocaust and mass atrocities do young people acquire before they engage in formal learning? And do curricula and textbooks adequately respond to gaps in intelligibility and coherency?